Dysglycemia in non-functioning pancreatic neuroendocrine tumors (NF-PNET): Further insights into an under recognized entity - Osher, Esther; Geva, Ravit; Wolf, Ido; Tordjman, Karen; Klausner, Joseph; Sofer, Yael; Scapa, Erez; Shibolet, Oren; Ben –Ami Shor, Dana; Bar-Yishay, Iddo; Lubezky, Nir; Goykhman, Yaacov; et al. (Journal of clinical & translational endocrinology, 2023)
•Pancreatic neuroendocrine tumors (PNETs) are rare, but their incidence has risen significantly in recent years.•Diabetes mellitus (DM) is clearly recognized in association with chronic pancreatitis and pancreatic cancer, but it has not been well-characterized in relation to non-functioning (NF)- PNETs.•We found a high rate of impaired glucose metabolism, either DM or Pre-DM, in a large cohort of subjects with NF-PNETs.•The high prevalence of diabetes/pre-diabetes was not related to obesity or tumor size.•The study highlights and reinforces the increased rate and association of DM and pre-DM with NF-PNETS. In addition, it adds a novel piece of information by evaluating the effect of tumor size, grade and tumor location on this association. Pancreatic neuroendocrine tumors (PNETs) are rare, but their incidence has risen significantly in recent years. Whereas diabetes mellitus (DM) is recognized in association with chronic pancreatitis and pancreatic cancer, it has not been well-characterized concerning non-functioning (NF)-PNETs. Study aim:to determine whether NF-PNETs are associated with DM/ Pre-DM and characterize the features of this putative association. Retrospective study to evaluate rate of Pre-DM /DM in subjects with NF-PNETs. Study cohort of 129 patients with histologically confirmed NF-PNETs, ∼60% were men (M/F: 77/52). Abnormal glucose metabolism that preceded any treatment was seen in 70% of this cohort: overt DM in 34% and Pre-DM in 36% of the subjects. However, during follow-up, the overall prevalence rose to 80.6%, owing exclusively to newly diagnosed DM in subjects who received treatment. Patients with DM/Pre-DM were older (65 ± 11; 54 ± 14; p < 0.0001), the tumor was more commonly localized in the pancreatic body and tail (76.5% vs. 23.5% p = 0.03), while BMI (27 ± 6 vs. 28 ± 5 kg/m2), and tumor size (2.4 ± 2 vs. 2.9 ± 3.2 cm) were similar. The relative prevalence of DM in our cohort of NF-PNETs was 1.6 higher than that in the age and gender-adjusted general Israeli population (95 %CI: 1.197–2.212p = 0.03). We found a high rate of impaired glucose metabolism, either DM or Pre-DM, in a large cohort of NF-PNETs. The high prevalence of diabetes/pre-diabetes was unrelated to obesity or tumor size. This observation should increase awareness of the presence of DM on presentation or during treatment of “NF”-PNETs.